Website-Based Expert System for Diagnosing Epilepsy in Children Using the Forward Chaining Method - Nasser, Rahmawati; Subhan, Subhan; putri, iin karmila (Universitas Bumigora Mataram-Lombok, 2024)
Information technology has been used in various sectors of life, including the health sector. One of them is the use of expert systems in diagnosing disease. Disease diagnosis carried out by an expert has weaknesses along with the expert's biological weaknesses. One technology that can be a solution is an expert system. This research aims to build a web-based expert system for diagnosing epilepsy in children, along with things that parents can do when treating epilepsy patients. The method used in this research is forward chaining, and system testing is carried out using the Black Box method. From the system design that has been created and tested, a web-based expert system application for diagnosing epilepsy in children has been produced. The black-box testing results show that all menus function well and as expected. The results of expert testing and user testing results obtained a final score of 3.8, which means the assessment is in the very suitable category. Apart from that, it will provide information and education to the public, in this case, the parents of epilepsy patients, regarding the type of epilepsy the child suffers from and how to treat it, which can be accessed anywhere and at any time.